EFFECT OF DIFFERENT MATERIALS ON FOAM PADS USED IN MODIFIED CLINICAL TEST OF SENSORY INTERACTION ON BALANCE (MCTSIB) FOR BALANCE IN INDIVIDUALS WITH VESTIBULAR DYSFUNCTION. (Cuestiones de Fisioterapia, 2025)
Introduction Vestibular dysfunction affects a significant number of individuals, leading to dizziness and balance impairment. Population studies indicate that approximately 1.6% of individuals experience peripheral vestibular disorders. The Modified Clinical Test of Sensory Interaction on Balance (mCTSIB) is widely used to assess a patient’s dependence on sensory inputs for balance and to customize rehabilitation strategies accordingly.